The Effects of the Seven Habits Program for Developing, Learning Goal Setting of Seventh Grade Students at Khlongkhlungratrangsan School in Kamphaeng Phet Province - Lubbha, Arthittaya; Hatthasak, Manasanan (Academic MCU Buriram Journal, 2023)
The purpose of this research were: to study the effects of the seven habits program for developing, learning goal setting of seventh grade students at Khlongkhlungratrangsan school in Kamphaeng Phet province. This research was the quasi experimental research. The populations were 299 students of seventh grade in the second semester, academic year 2021 at Khlongkhlungratrangsan School in Kamphaeng Phet province. The researcher selected the sample group by cluster sampling from two classes that scores were not different by using learning goal setting test. Then random assignment was used; one was an experimental group consisting of 33 students and the other was a control group consisting of 36 students. The experimental group participated in the program for 10 sessions, 50 minutes per each session. The instruments used in this research were: 1) the seven habits program for developing, learning goal setting, 2) learning goal setting test, 3) the student’s self-report in each session, 4) the student’s opinion questionnaire toward the seven habits program for developing, learning goal setting of seventh grade students and the researcher. Mean, standard deviation, Parametric Statistics Paired-Sample t-test and Parametric Statistics Independent-Sample t-test were utilized for analyzing data. The research results found that: 1. The post-test scores from the learning goal setting test of the experimental group students, who used the seven habits program for developing, learning goal setting, were significantly higher than their pre-test scores at the .05 level of statistical significance. 2. The post-test scores from the learning goal setting test of the experimental group students, who used the seven habits program for developing, learning goal setting, were significantly higher than the posttest scores of the control group at the .05 level of statistical significance.